The Teachers Exploring Students’ Speaking Skill using Hypnoteaching - Rahmaniah Rahmaniah; Abdul Rohman (Borneo Educational Journal (Borju), 2020)
Hypnoteaching could be a “new” strategy or procedure in education, especially in the teaching and learning process. Furthermore, hypnoteaching was an activity in which the teacher gave affirmative or positive words. Hypnosis is usually described or done with a conscious state where. In teaching, hypnosis collaboration with the activity is that the teacher gave a positive word to students. This study was conducted in M.A. Sabillarasyad. To found the result in this study researcher used interviews were as an instrument to collect the data. The subjects in this study are three teachers. The result showed that students’ speaking problems were reduced, and the students were more confident after the teacher used hypnoteaching, in which the teachers gave positive words to students by repetition. Furthermore, the students more relax and enjoy the learning process. The researcher found the HT1 as the teacher one used hypnoteaching in order for students focused on there did not aware when the teacher did hypnoteaching. Therefore the students feel more closely with the teacher when their inside or outside the class. The researcher concludes that Hypnoteaching was a suitable method for reducing students’ speaking problems and helped the teacher manage the classroom in the learning process.